Using Story Frame Approach to Increase Students’ Reading Comprehension at Senior High School - Nurlia, Putri; Ramadhona, Sri; Devita , Sinta Dwi (UPT. Pengembangan Bahasa IAIN Zawiyah Cot Kala Langsa, 2020)
Using the Story Structure Approach to Increase Students. Reading Comprehension at the tenth grade of SMAN 2 Kejuruan Muda. This research was conducted on the Story Frame technique to improve students' awareness of reading. It was done in the Senior High School. This research used a quantitative approach with an experimental class and a control class needed. As the sample, there were 28 students in each experimental and control classes. Test and observation were used in the data collection technique. Then the result of the test will score by using analytic score and the researchers used